A critical study on impact damage simulation of IM7/8552 composite laminate plate - Cui, Hao; Thomson, Daniel; Eskandari, Sina; Petrinic, Nik (Elsevier, 2019)
Plate impact tests on IM7/8552 composite laminates with different projectile 10 incident angles and velocities were carried out. Numerical simulations were conducted to 11 predict the impact damage, with both Puck and LaRC failure criteria having been employed in 12 this study. The dynamic failure performance of IM7/8552 lamina was reviewed first, by 13 referring to data obtained from experiments conducted at a range of strain rates. The 14 performance of the assessed modelling approaches was evaluated by comparing the results 15 of simulations against experimentally (quantitatively and qualitatively) acquired projectile 16 velocity, impact load and the failure modes of the plates. It proved to be challenging to model the macroscopic damage of the laminate at elevated projectile velocities; further 18 improvement can be made through enriching the dynamic material data and mitigating the 19 mismatch between the complex fibre architecture and its numerical representation.
Keywords: Composites; Plate impact; Numerical simulation; Modelling